Analysis of the Role of Innovation and Digitalization in Increasing Company Competitive Advantage in the Digital Economy Era - Hendrawati Hamid (PT. Anagata Sembagi Education, 2025)
This research aims to analyze the role of innovation and digitalization in enhancing the competitive advantage of companies in the digital economy era. The findings reveal that innovation, in terms of products, processes, and business models, has a significant impact on a company's competitiveness. Digital technologies such as artificial intelligence, big data, and the Internet of Things (IoT) enable companies to create added value, enhance customer experience, and accelerate adaptation to market changes. Digitalization, with a high adoption rate, plays a larger role in optimizing internal operations and expanding market reach. The study also indicates that manufacturing and services sectors have different approaches to implementing digitalization, but both show significant improvements in competitiveness. The research concludes that companies that optimize innovation and digitalization have a stronger competitive position and can survive in the increasingly fierce global competition. However, challenges in digitalization implementation and digital capability development remain. Therefore, policies supporting digital skills development and funding access for innovation are crucial for accelerating digital transformation.